2011
DOI: 10.5792/ksrr.2011.23.3.164
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the Complete Radial Tear of the Anterior Horn of the Medial Meniscus in Rabbits: A Comparison between Simple Pullout Repair and Pullout Repair with Human Bone Marrow Stem Cell Implantation

Abstract: PurposeTo evaluate the degree of biological healing response that occurs between the anterior horn of the medial meniscus (MM) and the tibial plateau and investigate the biological healing response after injection of human bone marrow stem cells (hBMSCs) in a rabbit model.Materials and MethodsTwenty-five rabbits with a mean body weight of 2.5 kg were chosen for this study. On the left knee, a complete radial tear was made at the anterior tibial attachment site of MM and after removal of tibial cartilage, pullo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Shimomura et al found similar results using a MSC-seeded nanofibrous scaffold constructed to match the meniscus circumferential fibre structure, and they demonstrated a significant decrease in meniscus extrusion following repair 71. Conversely, Hong et al 72 did not find evidence of tissue healing or regeneration with bone marrow stem cell matrix implantation in animal medial meniscus root tears. In another preclinical study by Moriguchi et al ,73 synovial MSCs cultured in monolayers to develop a scaffold-free tissue matrix demonstrated repair of meniscus defects and reduction of chondral degeneration.…”
Section: Bodymentioning
confidence: 90%
“…Shimomura et al found similar results using a MSC-seeded nanofibrous scaffold constructed to match the meniscus circumferential fibre structure, and they demonstrated a significant decrease in meniscus extrusion following repair 71. Conversely, Hong et al 72 did not find evidence of tissue healing or regeneration with bone marrow stem cell matrix implantation in animal medial meniscus root tears. In another preclinical study by Moriguchi et al ,73 synovial MSCs cultured in monolayers to develop a scaffold-free tissue matrix demonstrated repair of meniscus defects and reduction of chondral degeneration.…”
Section: Bodymentioning
confidence: 90%
“…Previous studies have shown that transplantation of isolated human amniotic mesenchymal cells [], human bone marrow stromal cells (BMSCs) [, ], and others [] into rabbit knee joints does not elicit apparent inflammatory responses. However, in our study we observed lymphoplasmacytic infiltration and inflammation in both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Desando et al 31 investigated the potential of adipose tissueederived stem cells for meniscus repair, showing that these cells were able to improve healing of cartilage and meniscus defects in a rabbit osteoarthritis model. Finally, although all the studies mentioned point to the potential benefits of stem cell augmentation, in a meniscus pullout suture enhanced with human BMSCs versus simple sutures alone in a rabbit model, Hong et al 32 did not show significantly increased healing in the group treated with suture and cells versus cells alone.…”
Section: Preclinical In Vivo Studies 2009 To 2014mentioning
confidence: 95%